Impact Of Self-Stigma and Self-Esteem on The Quality of Life of Mentally Ill Out-Patients of Obafemi Awolowo Teaching Hospital, In Ile Ife, Osun State, Nigeria - Oladejo , Ademola Sikiru; Oladejo , Ademola Sikiru; Akpunne , Bede Chinonye; Olasubomi , Olatunde Hammed (Corpus Intellectual, 2025)
Quality of life (QoL) is a broad concept that encompasses various aspects of an individual’s well-being, including physical health, psychological state, level of independence, social relationships, personal beliefs, and their relationship to salient features of their environment. The quality of life (QoL) of mentally ill out-patients in Nigeria faces several unique challenges. For this purpose, this research examines how selfstigma and self-esteem influence the quality of life of mentally ill out-patients of Obafemi Awolowo Teaching Hospital, in Ile Ife, Osun State, Nigeria. Using a cross-sectional survey a total of 387 participants (234 male and 153 female) were purposively selected for the study. The participants responded to the Internalized Stigma of Mental Illness (ISMI), The Rosenberg Self-Esteem Scale (RSES), and the World Health Organization Quality of Life (WHOQOL) scale. The results of the analysis revealed that self-esteem (ꞵ= .09, t = 1.84, p < .05) significantly and independently predicted the quality of life of mentally ill out-patients of Obafemi Awolowo Teaching Hospital, in Ile Ife, Osun State, Nigeria. However, self-stigma (ꞵ= .03, t = .54, p > .05) did not significantly and independently predict the quality of life among mentally ill out-patients in Osun state. Further results showed that self-esteem and self-stigma [F (2,384) = 2.87, p >.05] did not reliably predict the quality of life among mentally ill out-patients in Osun state. Still, the combination of these two variables (self-esteem and self-stigma) accounted for an 18% variance in the dependent variable (R2 = .18). Based on the findings of this study, therapeutic interventions, support groups, and self-help strategies are valuable and recommended.